Adjuvant postoperative radiotherapy in colon cancer: Preliminary results of a study in phase JI - Torres, Miguel; García, Silvia; Tasende, Blanca; Santini, Alejandro; Apardian, Robert; Fazzino, Marisa; Gaggero, Fernando (Cirugía del Uruguay, 1997)
Radiation therapy has not been used extensively for treatment of colon cancer, either therapeutically or as adjuvant.